Hubungan Dukungan Keluarga dan Pengetahuan Manajemen Diri dengan Kadar Gula Sewaktu Pasien Diabetes Mellitus di Puskesmas Seputih Raman Kabupaten Lampung Tengah: The Relationship Between Family Support and Self-Management Knowledge with Random Blood Glucose Levels in Diabetes Mellitus Patients at Seputih Raman Public Health Center, Central Lampung Regency - Retna Eva Agustina; Wisnu Probo Wijayanto; Rice Hernanda; Sutrisno (Journal of Nursing Education and Practice, 2024)
Introduction: Uncontrolled blood sugar levels in diabetes mellitus (DM) patients over time will increase the risk of developing chronic complications. The prevalence of DM in Lampung Province is 1.37%, or 68,164 people. Meanwhile, in the working area of Seputih Raman Public Health Center, Central Lampung Regency, the DM prevalence in 2023 was 224 cases. Diabetes mellitus patients require support, particularly from their families, which plays a crucial role in their health status. Additionally, knowledge about self-management enhances the quality of recovery for patients, especially regarding self-control. Objectives: The research objective was to determine the correlation between family support and self-management knowledge with blood sugar levels in diabetes mellitus patients at Seputih Raman Public Health Center in Central Lampung Regency. Method: This was a quantitative study with an analytic survey design and a cross-sectional approach. The research was conducted from August to September 2024 at Seputih Raman Public Health Center, Central Lampung Regency. The population of this research consisted of 224 diabetes patients, with a sample size calculated to be 144 respondents. The sampling technique used was purposive sampling, and the instrument used was a questionnaire. Data analysis was conducted using the Chi-square test. Result: The results of the study showed a significant relationship between family support (p-value 0.000) and self-management knowledge (p-value 0.000) with blood sugar levels in people with diabetes mellitus. Conclution: There is a significant relationship between family support and self-management knowledge with blood sugar levels in diabetes mellitus patients.